Delamination of bonding Interface between benzocyclobutene (BCB) and silicon dioxide/silicon nitride. (October 2016) - Bu, Fan; Ma, Qing; Wang, Zheyao
Abstract: BCB is emerging as an attractive bonding adhesive for wafer bonding in 3-D integration. Although the bonding strength of BCB is satisfactory with the assist of adhesion promoter, it is found that BCB suffers from interface delamination in harsh chemical or thermal conditions. This paper proposes, at chemical bond level, that the mechanism of interface delamination in KOH solution is attributed to the decomposition of SiOSi bonds at the interface between substrates and AP3000 adhesion promoter as a result of hydrolysis. Silicon dioxide and silicon nitride films with various densities of SiH and SiN bonds are prepared, and the bond densities are measured using infrared spectroscopy. The corresponding interface delamination rates of these films and BCB in KOH solution are measured, and the relations between the bond densities and the delamination rates are obtained for silicon dioxide and silicon nitride. It shows that the delamination rates decrease with the increase in the densities of SiOSi. These results demonstrate that the decomposition of SiOSi in KOH is the main reason for BCB delamination, and increase in the density of SiOSi improves the bonding strength. Highlights: The delamination of BCB in KOH is attributed to the decomposition of Si-O-Si bonds. Delamination rates decrease with the increase in the densities of Si-O-Si. Increase in the density of Si-O-Si improves the bonding strength of BCB.